2000
DOI: 10.1002/(sici)1096-9845(200001)29:1<37::aid-eqe894>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of time-delay for control of civil engineering structures

Abstract: SUMMARYTime-delay is an important issue in structural control. Applications of unsynchronized control forces due to time-delay may result in a degradation of the control performance and it may even render the controlled structures to be unstable. In this paper, a state-of-the-art review for available methods of time-delay compensation is presented. Then, "ve methods for the compensation of "xed time-delay are presented and investigated for active control of civil engineering structures. These include the recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…One of the most commonly considered examples of a noninvertible transfer system is that of a pure time delay. A number of approaches have been suggested to compensate for a pure delay including polynomial extrapolation (Darby et al, 2002;Horiuchi & Konno, 2001;Wallace et al, 2005a,b), adaptive forward prediction (Darby et al, 2002;Wallace et al, 2005b,b) and Smith's predictor (Agrawal & Yang, 2000;McGreevy et al, 1998;Reinhorn et al, 2004).…”
Section: +44 (117) 929 4423mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most commonly considered examples of a noninvertible transfer system is that of a pure time delay. A number of approaches have been suggested to compensate for a pure delay including polynomial extrapolation (Darby et al, 2002;Horiuchi & Konno, 2001;Wallace et al, 2005a,b), adaptive forward prediction (Darby et al, 2002;Wallace et al, 2005b,b) and Smith's predictor (Agrawal & Yang, 2000;McGreevy et al, 1998;Reinhorn et al, 2004).…”
Section: +44 (117) 929 4423mentioning
confidence: 99%
“…Although the technique was developed in the process industry to overcome problems in controlling timedelay systems, it has been suggested (Agrawal & Yang, 2000;McGreevy et al, 1998;Reinhorn et al, 2004) as method of overcoming time delay in transfer systems. Unfortunately, Smith's predictor has serious limitations for AbHWiL/RTDS.…”
Section: Emulator-based Controlmentioning
confidence: 99%
“…Agarwal and Yang [18] propose a compensator to decrease specified delay for control of civil engineering structures. However, their compensation technique does not guarantee performance and stability for systems having long time-delays.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm was tested using various magnitudes of time delay and various control gains. The results showed that the algorithm was effective in controlling the response of various inelastic structures, but decreased in efficiency with increased time delay due to the control force being applied out of phase with the structural displacement [Agrawal and Yang 2000].…”
Section: Introductionmentioning
confidence: 99%